2016
DOI: 10.1590/1518-8345.0686.2813
|View full text |Cite
|
Sign up to set email alerts
|

Quality of nursing documentation before and after the Hospital Accreditation in a university hospital

Abstract: Objective:to analyze the quality of nursing documentation by comparing the periods before and after the preparation for the hospital accreditation, using the Quality of Nursing Diagnoses, Interventions and Outcomes - Brazilian version (Q-DIO- Brazilian version). Method:observational study of interventions conducted in a university hospital. Nursing documentation of 112 medical records for the period before and 112 for the period after the hospital accreditation were compared using the Q-DIO instrument - Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 17 publications
(30 reference statements)
1
24
0
23
Order By: Relevance
“…NCS use is crucial to the provision of a safe nursing care, as it provides nurses with technical, scientific and human resources, improves the quality of care provided to the client and enables the recognition and appreciation of nursing in society (3)(4)(5)(6) . Thus, in addition to collaborating for a safe nursing care, NCS and NP integration, once implemented and performed properly, collaborate to carry out academic research, legal analysis, auditing of accounts and general analysis of levels of quality of care of nursing (7) .…”
Section: Introductionmentioning
confidence: 99%
“…NCS use is crucial to the provision of a safe nursing care, as it provides nurses with technical, scientific and human resources, improves the quality of care provided to the client and enables the recognition and appreciation of nursing in society (3)(4)(5)(6) . Thus, in addition to collaborating for a safe nursing care, NCS and NP integration, once implemented and performed properly, collaborate to carry out academic research, legal analysis, auditing of accounts and general analysis of levels of quality of care of nursing (7) .…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian study analyzed the quality of nursing records before and after hospital accreditation. Among the data evaluated, it was possible to identify that the dimension "Nursing Diagnoses as Product" did not present differences before and after intervention (p=0.002) (20) . However, in this study, all items showed improvement after the intervention (p=0.006).…”
Section: Discussionmentioning
confidence: 97%
“…A significant improvement in the quality of nursing records was observed in 24 of the 29 items (82.8%) of the questionnaire. (20) The institution maintains the study group as a continuous strategy to improve the quality of nursing records, the Nursing Process and standardized language systems in electronic medical records.…”
Section: Discussionmentioning
confidence: 99%
“…A documentação em prontuário destacou-se como uma prática essencial ao enfermeiro, tendo importância clínica e legal e constituindo-se em importante ferramenta de comunicação entre os profissionais de enfermagem e da saúde. No cuidado da pele, cabe ao enfermeiro e equipe realizarem registros que reflitam a assistência ao paciente de forma clara, completa e fidedigna, de forma a garantir continuidade, segurança e qualidade do cuidado (6,(12)(13) .…”
Section: Discussionunclassified